Prenatal Screening and Diagnosis: Time for a Paradigm Shift - Oyelese, Yinka; Schioppo, Davia; O'Brien, Barbara (American Journal of Perinatology, 2024)
Recent advances in genetics and imaging have ushered substantial breakthroughs in screening and diagnosis for chromosomal and structural abnormalities. Thus, it is imperative that health care providers caring for pregnant individuals should reexamine established practices in prenatal screening and diagnosis. In the past, screening for chromosomal abnormalities was based almost entirely on Down syndrome. Pregnant individuals aged > 35 years were considered at “high risk” or of “advanced maternal age” based on age alone; however, the advent of tests with high sensitivity for prenatal detection of chromosomal abnormalities should lead to abandoning that concept, at least from the perspective of chromosomal abnormalities. Given that first-trimester and second-trimester screenings will fail to detect between 5 and 20% of Down syndrome, in most situations, noninvasive testing with cell-free DNA should be the first-line screen for Down syndrome. The fact that over 99% of fetuses with Down syndrome will be detected prenatally with cell-free DNA gives other fetal chromosomal and structural abnormalities increasing prominence. Chromosomal microarray analysis (CMA) permits prenatal detection of several clinically important chromosomal aberrations that cannot be detected by karyotype and may exist in structurally normal fetuses with low-risk cell-free DNA screening. As such, CMA should be more readily conducted when invasive testing is performed, regardless of the presence of a structural abnormality. Isolated sonographic “soft markers” have no clinical significance in patients who have normal cell-free DNA screening, can cause unwarranted anxiety and a negative impact on pregnancy, and perhaps it is time to stop discussing them. Detailed first-trimester ultrasound allows early detection of several severe fetal anomalies and, therefore, in settings with adequately trained personnel and resources, should be used more frequently. This opinion traces the evolution of prenatal screening and diagnosis and advocates for a paradigm shift that aligns with recent developments in prenatal screening and diagnostic capabilities.Key Points
Keywords: prenatal screening; prenatal diagnosis; chromosomal aberrations; chromosomal microarray; noninvasive prenatal screening; karyotype